1957
DOI: 10.1136/bmj.2.5042.451
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Acute Primidone Poisoning with Bemegride and Amiphenazole

Abstract: inflamed than the mucosa, and the cell reaction was largely polymorphonuclear. The outer surface showed peritonitis of apparently some days' duration. An occasional Grampositive coccus was seen. Special staining revealed amyloid deposits in small vessels and in the basement membrane. DiscussionThe diagnosis of peritonitis was based on the sudden onset of upper abdominal pain radiating to the right iliac fossa and acute abdominal tenderness, followed later by rigidity and absence of bowel sounds. In retrospect,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

1958
1958
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Clinical antagonism has been reported to such drugs as pentobarbitone, thiopentone, glutethimide, methyprylone, persedon, primidone, carbromal, and bromvaletone, either alone or occasionally combined with structurally unrelated hypnotics (Shulman, Shaw, Cass, and Whyte, 1955;Harris, 1955;Holten, 1956;Palmer, 1956;von Planta and Klingler, 1956;Dotevall and Herner, 1957).…”
Section: Physiology Department University Of Melbournementioning
confidence: 99%
See 2 more Smart Citations
“…Clinical antagonism has been reported to such drugs as pentobarbitone, thiopentone, glutethimide, methyprylone, persedon, primidone, carbromal, and bromvaletone, either alone or occasionally combined with structurally unrelated hypnotics (Shulman, Shaw, Cass, and Whyte, 1955;Harris, 1955;Holten, 1956;Palmer, 1956;von Planta and Klingler, 1956;Dotevall and Herner, 1957).…”
Section: Physiology Department University Of Melbournementioning
confidence: 99%
“…
The article by Dotevall and Herner (1957) has prompted us to summarize some recent pharmacological observations concerning the safe and widespread analeptic activity of bemegride to hypnotics both structurally related and unrelated to it.Bemegride (f8-methyl-fi-ethylglutarimide) will wake mice from moderately deep acute hypnosis (ready response to pain, moderate depression of corneal reflex, sleeping time 60-80 minutes) due to such structurally related hypnotics as barbiturates (pentobarbitone), thiobarbiturates (thiopentone), glutarimides (glutethimide; " doriden " and others), diketopiperidines (methyprylone; "noludar "), diketotetrahydropyridines (" persedon"), diketothiazanes (" dolitrone "), diketothiazolidines (5: 5-diethyl-2: 4-diketothiazolidine), monoureides (carbromal and bromvaletone), and succinimides (5-
…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Serious acute intoxication with primidone has been reported in 7 adults attempting suicide (Arnold and Ceranke-Hofermayer, 1953;Bogan, Rentoul, and Smith, 1965;Del Greco and Arieff, 1962;Dotevall and Herner, 1957;Fazekas and Renger, 1960; Morley and Wynne, 1957;Sciarra et al, 1954), 3 of whom succeeded (Bogan et al, 1965;Fazekas and Renger, 1960;Morley and Wynne, 1957). The lethal dose in each case was 20-30 g.; but 2 of the 4 survivors had also ingested 25-30 g. Accidental intoxication with primidone has been reported once in adults (Ajax, 1966), and twice in children (Gellman, 1965;Morley and Wynne, 1957).…”
mentioning
confidence: 99%
“…Sundberg, R. D. (1955 Since bemegride (l/3-methylethylglutarimide) was introduced by Shaw et al in 1954, there has been much discussion on whether this drug is a specific antagonist to the barbiturates or a non-specific central analeptic. Many papers have described the stimulating effect of bemegride in barbiturate coma (Shulman et al, 1955;Clemmesen, 1956), but more recent reports have suggested that it appears to have a restorative action in coma due to non-barbiturate sedatives, such as primidone (Dotevall and Herner, 1957) and glutethimide (Rowell, 1957). The factors which influence the outcome in patients suffering from sedative poisoning are so varied that it is impossible to assess the specificity of action of bemegride in such circumstances.…”
mentioning
confidence: 99%